2018
DOI: 10.14778/3229863.3236253
|View full text |Cite
|
Sign up to set email alerts
|

ProvSQL

Abstract: This demonstration showcases ProvSQL, an open-source module for the PostgreSQL database management system that adds support for computation of provenance and probabilities of query results. A large range of provenance formalisms are supported, including all those captured by provenance semirings, provenance semirings with monus, as well as where-provenance. Probabilistic query evaluation is made possible through the use of knowledge compilation tools, in addition to standard approaches such as enumeration of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Senellart et al developed an open-source module for the PostgreSQL database management system. The module developed by them adds support for the computation of provenance and probabilities of query results [11]. Garima et al presented a framework named HUKA that uses provenance polynomials for tracking the derivation of query results over knowledge graphs by encoding the edges involved in generating the answer [18].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Senellart et al developed an open-source module for the PostgreSQL database management system. The module developed by them adds support for the computation of provenance and probabilities of query results [11]. Garima et al presented a framework named HUKA that uses provenance polynomials for tracking the derivation of query results over knowledge graphs by encoding the edges involved in generating the answer [18].…”
Section: Related Workmentioning
confidence: 99%
“…To address the pivotal research problem, Annolog is designed in this paper for usage either as a standalone reasoner or to work synchronously with the database management system engine. When evaluating a query on annotated data, it is advantageous to capture meta-information about the result of the query along with the result itself [11]. The annotated meta-information indicates the multiplicity and probability of the results, and why as well as how the outputs are generated.…”
Section: Introductionmentioning
confidence: 99%
“…P SQL is "an open-source module for the P SQL database management system that adds support for computation of provenance and probabilities of query results" [Senellart et al, 2018]. It supports where-provenance, semiring provenance, and m-semiring provenance (for negation and why-notprovenance).…”
Section: P Sqlmentioning
confidence: 99%
“…Kimmig et al (2017) showed that if the underlying logical theory is compiled into sd-DNNF representation T C, then we can solve weighted model counting instances over any semiring using polynomially (in |T C|) many additions and multiplications. This is also the strategy that current implementations like ProbLog (De Raedt et al, 2007), aspmc (Eiter, Hecher, & Kiesel, 2021) and ProvSQL (Senellart, Jachiet, Maniu, & Ramusat, 2018) predominantly employ. As Kimmig et al (2017) also noted, depending on the specific semiring in use, this is clearly far from the most efficient solution.…”
Section: Introductionmentioning
confidence: 99%